2014
DOI: 10.9790/487x-16120113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Competence Factor, Independence and Attitude against Professional Auditor Audit Quality Improve Performance in Inspectorate (Inspectorate Empirical Study in South Sulawesi Province)

Abstract: The aims of this research are to know the positive and significant effect among competence, independence and professional attitude partially and simultaneously to inspectorate work achievement South Sulawesi. This inspectoratecontrol is based on regional government implementation and conducted structurally from regency/city level, province to centre level. The independent variables in this research are competence, independence and professional attitude for dependent variable is inspectorate work achievement th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
5
0
5
Order By: Relevance
“…The widely used definition of audit quality is the definition by DeAngelo (1981), who defined audit quality as the likelihood that an auditor will both, find a breach in the client"s accounting system and report the breach. Despite the fact that there are diverse definitions of audit quality; there are generally two fundamental elements developed when evaluating the definition of quality, which are the auditor"s capability to both find and declare the misstatement and the auditor"s independent (Al-khaddash, Al Nawas and Ramadan, 2011; Usman, Sudarma, Habbe and Said, 2014;Sulanjaku andShngjergji, 2015 andOctavia andWidodo, 2015). DeFond and Zhang (2013) believe that the higher the audit quality, the "greater assurance of high financial reporting quality.…”
Section: Definition Of Audit Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…The widely used definition of audit quality is the definition by DeAngelo (1981), who defined audit quality as the likelihood that an auditor will both, find a breach in the client"s accounting system and report the breach. Despite the fact that there are diverse definitions of audit quality; there are generally two fundamental elements developed when evaluating the definition of quality, which are the auditor"s capability to both find and declare the misstatement and the auditor"s independent (Al-khaddash, Al Nawas and Ramadan, 2011; Usman, Sudarma, Habbe and Said, 2014;Sulanjaku andShngjergji, 2015 andOctavia andWidodo, 2015). DeFond and Zhang (2013) believe that the higher the audit quality, the "greater assurance of high financial reporting quality.…”
Section: Definition Of Audit Qualitymentioning
confidence: 99%
“…In addition, Usman et al, (2014) indicated that the public sector audit procedure is similar to the private sector audit. The distinction is in the political influence of the nation concerned and government policy.…”
Section: Definition Of Audit Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini berarti variabel independensi berpengaruh positif dan signifikan terhadap kualitas audit pada Kantor Akuntan Publik di Kota Denpasar. Hasil penelitian ini bersesuaian dengan Imron dkk., (2017), Tepalagul dan Lin (2015),Usman et al, (2014) danHosseinniakani et al, (2014) dalam penelitiannya menyatakan bahwa independensi berpengaruh terhadap kualitas audit. Penelitian ini juga sejalan dengan penelitian yang dilakukan(Badjuri, 2011) yang menyatakan bahwa independensi berpengaruh positif terhadap kualitas audit.…”
unclassified
“…Faktor yang dapat mempengaruhi kinerja auditor adalah profesionalisme yang dapat diartikan sebagai sikap profesional sering dinyatakan dalam literatur, profesionalisme berarti bahwa orang bekerja secara professional (Hudiwinarsih, 2010). Profesionalisme meliputi kemampuan penguasaan baik secara teknis, maupun secara teoritis bidang keilmuan dan keterampilan yang berhubungan dengan tugasnya sebagai pemeriksa (Asri et al, 2014). Menjaga kepercayaan menjadi kewajiban auditor dihadapan klien maupun pihak ketiga dengan senantiasa meningkatkan keahlian profesionalnya (Mu'azu dan Siti, 2013).…”
unclassified